2007
DOI: 10.1038/bdj.2007.124
|View full text |Cite
|
Sign up to set email alerts
|

Pre-sterilisation cleaning of re-usable instruments in general dental practice

Abstract: In many dental practices, the cleaning of re-usable dental instruments is undertaken using poorly controlled processes and procedures, which increase the risk of cross infection. Clear and unambiguous advice must be provided to the dental team, especially dental nurses, on appropriate equipment, chemicals and environment for cleaning dental instruments. This should be facilitated by appropriate training programmes and the implementation of quality assurance procedures at each stage of the cleaning process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 17 publications
0
34
0
4
Order By: Relevance
“…However, the extent of compliance with recommended procedures in general practice and the effectiveness of the procedures is generally not known, although in some cases the lack of compliance has been demonstrated -studies by Bagg et al (2001 and2007) indicated that compliance with recommended practice in cleaning dental instruments was poor in a number of surgeries, indicating a need for better education of clinicians and nursing staff. The results from this study showed that before use, approximately 40 % of units were contaminated and after they had been used in the clinic approximately 64 % were contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of compliance with recommended procedures in general practice and the effectiveness of the procedures is generally not known, although in some cases the lack of compliance has been demonstrated -studies by Bagg et al (2001 and2007) indicated that compliance with recommended practice in cleaning dental instruments was poor in a number of surgeries, indicating a need for better education of clinicians and nursing staff. The results from this study showed that before use, approximately 40 % of units were contaminated and after they had been used in the clinic approximately 64 % were contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…Ces différentes études soulignent l'importance du respect des procédures d'hygiène et des démarches de mise sous assurance qualité des procédures et techniques utilisées pour retraiter toute l'instrumentation utilisée lors des actes dentaires [26].…”
Section: Discussionunclassified
“…Dental care faces a number of pragmatic issues. Studies carried out clearly demonstrated that decontamination in dentistry is often not given the consideration or investment that it requires (71,72) . In many cases decontamination in dental clinics is carried out in the same room as where the patient is treated.…”
Section: Example Of New Endoscopy Washersmentioning
confidence: 99%